Watercolour mountains : start to paint with 3 colours, 3 brushes and 9 easy projects - Palmer, Matthew (Artist) (Take three colours, 2019)
Even if you've never picked up a paintbrush, Matthew Palmer will show you how to paint convincing watercolor mountain scenes using just 3 colors, 3 brushes, a plastic palette and a watercolor pad. From only 3 affordable watercolor paints in red, blue and yellow you can mix a huge range of colors and paint beautiful landscapes you'll be proud to hang on your wall. Starting from the simplest of mountain scenes, Matthew builds your skills as you progress through the 9 easy projects in the book, and by the end you'll be amazed at what you have achieved. Clear instructions and step-by-step photographs show you how to add detail, shadow and distance to a scene, and there are numerous handy tips and helpful 'jargon busters' to help you learn the basic watercolour techniques. Before you know it, you'll have acquired all the skills you need to paint your own wonderful mountain scenes in watercolour.